Assessment of Quality of Life in Patients Following Total Resection of Convexity Meningioma. - Panta, Saroj; Sapkota, Anita (Nepal Journal of Neuroscience, 2025)
Introduction: Meningioma is the most common type of benign intracranial tumor, representing nearly one-third of the primary brain tumors. Supratentorial convexity meningiomas are the most amenable to gross total resection owing to their favorable location and operative outcome.Despite the resection and radiological cure, a significant number of patients continue to face troubling postoperative conditions, which include cognitive dysfunction, emotional disturbances, fatigue, and deficits in various social and work activities. These functional and psychosocial outcomes, particularly postoperative QoL, remain scantily documented in the literature. So, a comprehensive evaluation of postoperative QoL is essential to understand the broader impact of the disease and its treatment on patient well-being, and to guide holistic, patient-centered care beyond tumor removal. This study aims to evaluate the quality of life (QoL) in patients with supratentorial convexity meningiomas who have undergone total excision, and to compare their outcomes with those of healthy controls.Material & Methods: A prospective observational study was conducted. Thirty patients with radiologically confirmed total excision of supratentorial convexity meningiomas were evaluated at 3 months post-surgery. QoL was assessed using SF-36 and Lawton’s IADL scale. Thirty cases were taken as a control. Statistical analysis was done.Results: The cases demonstrated significantly reduced scores in SF-36 domains, including physical functioning, role limitations (physical and emotional), social functioning, pain, and general health (p